2018
DOI: 10.1093/nar/gky345
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative recognition of T:T mismatch by echinomycin causes structural distortions in DNA duplex

Abstract: Small-molecule compounds that target mismatched base pairs in DNA offer a novel prospective for cancer diagnosis and therapy. The potent anticancer antibiotic echinomycin functions by intercalating into DNA at CpG sites. Surprisingly, we found that the drug strongly prefers to bind to consecutive CpG steps separated by a single T:T mismatch. The preference appears to result from enhanced cooperativity associated with the binding of the second echinomycin molecule. Crystallographic studies reveal that this pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…A single hydrogen-bonded anti–syn arrangement is observed in G3:G14 of CPX2, where the stability to the more distant anti–syn base pairing is compensated via the water-mediated interaction between the mismatched bases (Figure 6B). Previous studies also showed that two mismatches with larger opening angles including T:T and C:T can be reinforced by water-mediated pairing to enhance the overall structural stability of the ligand–DNA interactions (61,67). Notably, in CPX3, G3:G14 has the most unusual base pairing, in which the G3 adopts a syn like conformation based on the unusual ‘χ’ value of 147° yet G3 exhibits a C1′- exo pucker most usually associated with syn geometry (Figure 6C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single hydrogen-bonded anti–syn arrangement is observed in G3:G14 of CPX2, where the stability to the more distant anti–syn base pairing is compensated via the water-mediated interaction between the mismatched bases (Figure 6B). Previous studies also showed that two mismatches with larger opening angles including T:T and C:T can be reinforced by water-mediated pairing to enhance the overall structural stability of the ligand–DNA interactions (61,67). Notably, in CPX3, G3:G14 has the most unusual base pairing, in which the G3 adopts a syn like conformation based on the unusual ‘χ’ value of 147° yet G3 exhibits a C1′- exo pucker most usually associated with syn geometry (Figure 6C).…”
Section: Discussionmentioning
confidence: 99%
“…reported that the bis-intercalator echinomycin preferentially binds to consecutive CpG steps separated by a T:T mismatch, causing a smooth bend (roll angle c.a. −3°), caused by the stacking interactions starting at the thymines of the sheared T:T base pair through the quinoxaline ring of echinomycin and ending at the guanines of the flanking G:C base pairs (67) (Figure 7D). The kinked DNA structure induced by anticancer drugs such as cis platin and oxaliplatin has been found to play a significant role in the cytotoxic actions of these compounds (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…The structural bases behind this interaction have been extensively studied ( 80–82 ). However, recently our group found that echinomycin prefers to bind to consecutive CpG steps separated by a T:T mismatch rather than perfect DNA duplexes (Figure 7G ) ( 83 ). Detailed structural analysis showed that echinomycin induces deformation in the mismatched DNA duplex, allowing cooperative recognition of the T:T mismatch by a second echinomycin molecule.…”
Section: Ligand-induced Structures Of the Dna Duplexmentioning
confidence: 98%
“…6 The mechanism of action of echinomycin is attributed to the bis-intercalation and binding with high affinity to the 5 0 -CG bases of DNA, which prevent the unwinding of the double helical DNA; thus, inhibiting the replication of chromosomal DNA. 4,7,8 Furthermore, it is a potent inhibitor of the hypoxia-inducible factor-1 (HIF-1) DNA-binding, a factor that controls genes necessary in tumor biology including cell growth, glycolysis, angiogenesis, metastasis, and invasion. 7 Unfortunately, no signicant response was observed in clinical trials conducted on patients suffering from metastatic so tissue sarcoma, advanced breast cancer, squamous cell cervical carcinoma, advanced ovarian cancer, advanced renal carcinoma, central nervous system, and colorectal cancer due to its high dose-related toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…7 Unfortunately, no signicant response was observed in clinical trials conducted on patients suffering from metastatic so tissue sarcoma, advanced breast cancer, squamous cell cervical carcinoma, advanced ovarian cancer, advanced renal carcinoma, central nervous system, and colorectal cancer due to its high dose-related toxicity. [8][9][10][11][12][13][14][15][16][17][18][19][20] One of the most common side effects is related to echinomycin in gastrointestinal tract symptoms, including moderate to severe nausea, vomiting, and diarrhea, as well as the elevation of hepatic enzymes and a mild decrease in platelets and granulocyte counts which was lifethreading in some cases. 11,21 Accordingly, in all clinical trials, no dose escalation was possible to achieve a signicant clinical response.…”
Section: Introductionmentioning
confidence: 99%